A human serum‐enriched medium formulation supports high viability and marker expression in primary melanocyte cultures from the outer root sheath and epidermis. Issue 1 (2nd November 2017) - Schneider, Marie; Lohrenz, Andrea; Cross, Michael; Hacker, Michael C.; Simon, Jan C.; Savkovic, Vuk
Abstract: Formulating clinically relevant melanocyte cultivation media that maintain the balance between proliferation and maturation to functional melanocytes is a major experimental and regulatory challenge. Within the translation of human melanocytes from the outer root sheath of human hair follicle (HUMORS), we developed a melanocyte medium free of chemical mitogens, chemical melanogenesis enhancers and bovine products, enabling proliferation as well as melanotic differentiation. The formulation involved the replacement of bovine pituitary extract (BPE) and bovine serum (FBS) with human serum (HS) combined with ascorbic acid, CaCl2, epinephrine, L‐glutamine, insulin and fibroblast growth factor. The cultivation efficiency was characterized through proliferation and exertion of melanotic phenotype, gene and protein expression of melanotic markers and melanin content. Having established an application‐directed BPE‐free formulation, we then re‐formulated a research‐grade medium with BPE for purposes of even more effective in vitro cultivation, adjusted to specific requirements of HUMORS and normal human epidermal melanocytes (NHEM).